Connections, connections, connections the weights of presidential endorsements and total expenditures in 2019 Philippine midterm election outcomes - Balita, Kyla Gabrielle M.; Cajayon, Mary Joyce Anne V.
Political campaigns and their successes appear to hinge on various factors, depending on the context. Researchers have conducted studies on the impact of candidates’ family networks, social and celebrity statuses, and genders, among other things, on voter perception in Philippine elections. Given the limited scope of existing literature, this study seeks to assess the weights of two other determinants— endorsements by incumbent government officials, specifically President Rodrigo Duterte and Davao City mayor Sara Duterte-Carpio, and campaign expenditure —that possibly contributed to the vote tallies of specific candidates during the 2019 senatorial elections and create a model than can be used to predict candidate vote tallies. Several regression models are employed to gauge such effects. First, a logistic regression is used to produce probability predictions for endorsements and expenditures, as well as certain candidate attributes like sex, incumbency status, and dynastic links. Second, a multiple regression model including all variables is generated and assessed in terms of its fit to the data. Lastly, linear regressions are executed to check for robustness. The results show endorsements to be significant in predicting winning probabilities, and both endorsements and expenditures to be significantly robust in determining raw votes.